Coping with Crises: A Study of Humor Appeal in Moroccan Advertising during the COVID-19 - Chirig, Abdelkrim; Bouziane, Karima; Zakhir, Marouane (Information & Media, 2024)
Introduction. The emergence of COVID-19 prompted diverse advertising strategies globally, with humor appeal being one of the notable approaches. Method. Thus, the aim of this research is to examine and analyze the utilization of humor appeal in Moroccan advertising during the pandemic, employing a semiotic perspective. Analysis. The study adopts a qualitative approach and employs Barthes’ model of denotative and connotative meanings for analysis. Results. The findings indicate that when humor is employed contextually, it significantly enhances the impact of the advertisements. The study reveals the creativity and adaptability of Moroccan advertising agencies in utilizing humor appeal to engage audiences during the crisis. Conclusion. This research highlights the effectiveness of humor appeal in advertising during unprecedented times, providing insights into adaptive advertising strategies through a semiotic analysis of the Moroccan context.
Keywords: advertising; denotative meaning; connotative meaning; COVID-19; humor appeal; semiotic analysis